Meta-analysis of aberrant lymphatic drainage in recurrent breast cancer. Issue 12 (6th September 2016) - Ahmed, M; Baker, R; Rubio, I T
Abstract: Background: Sentinel node biopsy (SNB) in recurrent breast cancer offers targeted axillary staging compared with axillary lymph node dissection (ALND) or no treatment. The evidence for lymphatic mapping in recurrent breast cancer is reviewed, focusing on aberrant drainage and its implications for patient management. Methods: A meta-analysis of studies evaluating lymphatic mapping in recurrent breast cancer was performed. Outcomes included sentinel node identification, aberrant lymphatic pathways and metastatic node rates in aberrant drainage and ipsilateral axilla. Pooled odds ratios (ORs) and 95 per cent confidence intervals (c.i.) were estimated using fixed-effect analyses, or random-effects analyses in the event of statistically significant heterogeneity. Results: Seven studies reported data on lymphatic mapping in 1053 patients with recurrent breast cancer. The intraoperative sentinel node identification rate was 59·6 (95 per cent c.i. 56·7 to 62·6) per cent, and significantly greater when the original axillary surgery was SNB compared with ALND (OR 2·97, 95 per cent c.i. 1·66 to 5·32). The rate of aberrant lymphatic drainage identification was 25·7 (23·0 to 28·3) per cent, and significantly greater when the original axillary surgery was ALND (OR 0·27, 0·19 to 0·38). The metastatic sentinel node rate was 10·4 (8·6 to 12·3) per cent, and a significantly greater metastatic nodal burden was identified in the ipsilateral axilla (OR 6·31, 1·03 to 38·79). Conclusion: Lymphatic mapping is feasible in recurrent breast cancer. It avoids ALND in over 50 per cent of patients who have undergone SNB, and allows the 4 per cent of patients with metastatically involved aberrant nodes to receive targeted surgical and adjuvant therapies. Abstract : Sentinel node biopsy feasible in most cases